'MY KIDNEYS, MY CHOICE, DECISION AID': SUPPORTING SHARED DECISION MAKING. Issue 2 (10th December 2014) - Fortnum, Debbie; Smolonogov, Tatiana; Walker, Rachael; Kairaitis, Luke; Pugh, Debbie
SUMMARY Background For patients with chronic kidney disease (CKD) who are progressing to end‐stage kidney disease (ESKD) a decision of whether to undertake dialysis or conservative care is a critical component of the patient journey. Shared decision making for complex decisions such as this could be enhanced by a decision aid, a practice which is well utilised in other disciplines but limited for nephrology. Methods A multidisciplinary team in Australia and New Zealand (ANZ) utilised current decision‐making theory and best practice to develop the 'My Kidneys, My Choice', a decision aid for the treatment of kidney disease. Results A patient‐centred, five‐sectioned tool is now complete and freely available to all ANZ units to support the ESKD education and shared decision‐making process. Distribution and education have occurred across ANZ and evaluation of the decision aid in practice is in the first phase. Conclusions Development of a new tool such as an ESKD decision aid requires vision, multidisciplinary input and ongoing implementation resources. This tool is being integrated into ANZ, ESKD education practice and is promoting the philosophy of shared decision making.